Postsocialist Shrinking Cities - Wu, Chung-Tong; Gunko, Maria; Stryjakiewicz, Tadeusz; Zhou, Kai (Routledge Contemporary Perspectives on Urban Growth, Innovation and Change, 2022)
This book provides a comparative analysis of shrinking cities in a broad range of postsocialist countries within the so-called Global East, a liminal space between North and South. While shrinking cities have received increased scholarly attention in the past decades, theoretical, and empirical research has remained predominantly centered on the Global North. This volume brings to the fore a range of new perspectives on urban shrinkage, identifying commonalities, differences, and policy experiences across a very diverse and vivid region with its various legacies and contemporary controversial developments. With chapters written by leading experts in the field, insider views assist in decolonizing urban theory. Specifically, the book includes chapters on shrinking cities in China, Russia, and postsocialist Europe, presenting comparative discussions within countries and crossnational cases on theoretical and policy implications. The book will be of interest to students and scholars researching urban studies, urban geography, urban planning, urban politics and policy, urban sociology, and urban development.